PENGARUH SUMBER DAYA MANUSIA, PENGAWASAN KEUANGAN DAERAH, PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMITMEN ORGANISASI TERHADAP KEANDALAN PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Pada Satuan Kerja Perangkat Daerah Kabupaten Labuhan Batu) - Fransiska -; Nur Azlina; Susilatri - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the effect of human resource, Local Financial Monitoring, information technology utilization and commitmen organization to reliability of financial reporting Labuhan Batu regency government. The data in this study is the primary data obtained from questionnaires distributed directly to the respondents. Data collected from 67 respondents who are working at financial reporting staff in local work unit of Labuhan Batu regency government. The method of data analysis used to test the hypothesis with multiple regression analysis using the program SPSS version 20. The results of this study is showed that human resource, Local Financial Monitoring, information technology utilization and commitment organization influence in partial in the reliability of financial reporting in Labuhan Batu regency government. The magnitude of the effect caused by Adjusted R² by four variables is 62,8% of the dependent variable, while the remaining 37,2% is influenced by other independent variabel that are not observed in this study.Keywords: human resource, financial monitoring, information technology, commitmen and reliability financial